PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, PERILAKU BELAJAR, KOMPETENSI DOSEN, DAN FASILITAS PEMBELAJARAN TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Djoko Kristianto, F. Bayu Ady Nugroho, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The purpose of this research is to examine the influence of Emotional Intelligence, Intellectual Intelligence, Learning Behavior, Lecturer Competence, and Learning Facility on Partial Level of Accounting Understanding. This research uses survey method, with student population of Faculty of Economics of Private University in Solo Accredited B. Sampling technique using purposive sampling and judgment sampling. so that in get sample of student of Faculty of Economics Slamet Riyadi (UNISRI) and Setia Budi University (USB) and University of Tunas Development (UTP), and at least have to take at least semester V, so get sample of 95 student, because UTP cannot do research so that only UNISRI students and USB samples. The type of data used primary and secondary data. The analysis technique used multiple linear regression analysis, t test, F test, and coefficient of determination. The result of this research Emotional Intelligence and Learning Facility have no significant effect to the level of Accounting Understanding while Intellectual Intelligence, Learning Behavior, and Lecturer Competence have significant influence to the Level of Understanding of Accounting.Keywords: emotional intelligence, intellectual intelligence, learning behavior, lecturers competence, learning facility, accounting understanding level